Interests and international regimes: Explaining cooperation in Arctic disputes - Jorbenadze, Luka (Tartu Ülikool, 2020)
Since the end of the Cold War international politics in the Arctic have been characterized by unusual level of cooperation among states. More recently, climate change has allowed the states to increase their presence and activity in the region, making the Arctic increasingly relevant in world politics. This process has been reflected by growing attention from the academia to the dynamics of conflict and cooperation in the region. In order to contribute to the existing knowledge on the dynamics of conflict and cooperation in the Arctic, this thesis studies three disputes regarding delimitation in the Barents Sea; continental shelf claims in the central Arctic Ocean and the status of the Northern Sea Route. The thesis aims to explain why nations cooperate during disputes in the Arctic. The expectations, that the states cooperate based on compatibility of interests, while international regimes facilitate cooperation, are drawn from the functional theory of international regimes developed by Robert Keohane. Using qualitative content analysis, Arctic strategy documents of the countries are studied to determine the interests of the countries in the region in general and in regards to the disputes in particular. The same method is used to analyze the United Nations Convention on the Law of the Sea as an international regime. Using the results from those steps, developments of the three disputes are analyzed to find out if the states had complementary interests relevant to the disputes, if the states cooperated and if so, if the regime contributed to cooperation during the dispute. The thesis finds that the states had complementary interests relevant to the disputes in all three cases. The states cooperated and used the functions provided by the regime in those cases where the regime was available and they did not cooperate when the regime was not available. The findings confirm the expectations of the theory. https://www.ester.ee/record=b5356899*est